Sound Velocity Profile (SVP) inversion through correcting the terrain distortion - Jin, Shaohua; Sun, Wenchaun; Bao, Jingyang; Liu, Min; (China), Yang Cui (The International Hydrographic Review, 2015)
In this paper, mode vectors are obtained via the Empirical Orthogonal Function (EOF) based on real Sound Velocity Profiles (SVP) measurements. Through correcting the terrain distortion, reconstructed coefficients of SVPs are determined by Genetic Algorithm (GA) and then the inversion result of the SVP is obtained. The conclusions show that the terrain distortion caused by sound velocity errors can be effectively corrected by the inversion result of the SVP. Using this process, the accuracy and processing efficiency of multi-beam bathymetry data can be significantly improved.